EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu